COMPARATIVE LINGUO-PRAGMATIC ANALYSIS OF PROMPT ENGINEERING STRATEGIES IN ENGLISH AND UZBEK (SCIENCE TIME JOURNAL, 2026)
This article presents a comparative linguo-pragmatic analysis of prompt engineering strategies in English and Uzbek AI-mediated communication. The study examines the syntactic structures, pragmatic intentions, speech acts, address strategies, and semantic precision of prompts generated by users while interacting with artificial intelligence systems. The findings reveal that English prompts tend to employ direct imperative constructions and structurally explicit patterns, whereas Uzbek prompts demonstrate greater contextual dependency, indirectness, and pragmatic politeness. A prompt corpus generated through ChatGPT interactions was analyzed using comparative and discourse-analytical approaches, resulting in the development of a comparative model of AI communication strategies in English and Uzbek. The study demonstrates that prompt engineering is emerging as a new linguistic phenomenon within contemporary digital discourse and AI-mediated interaction.